Two-stage mineral dissolution and precipitation related to organic matter degradation: Insights from in situ C–O isotopes of zoned carbonate cements. (February 2021) - Sun, Funing; Hu, Wenxuan; Wu, Haiguang; Fu, Bin; Wang, Xiaolin; Tang, Yong; Cao, Jian; Yang, Shengchao; Hu, Zhongya
Abstract: Mineral dissolution and precipitation, particularly of carbonate minerals, are ubiquitous and significant diagenetic processes in sedimentary rocks. However, the impacts of organic matter degradation on these processes in single systems remain unclear because the timing and fluid sources during progressive burial are poorly constrained. To address this issue, in situ C–O isotope analyses were conducted for zoned dolomite–ankerite/calcite cements from the Permian Lucaogou Formation in the Junggar Basin, China, using secondary ion mass spectrometry (SIMS) combined with mineralogical and elemental analyses. Carbonate minerals can be divided into early-stage and late-stage precipitations based on distinct variations in δ 18 O (−18.3 to −0.7‰ V-PDB), δ 13 C (−3.6 to +20.8‰ V-PDB), and Fe content (Fe# ranging from 0.002 to 0.373). The chemo-isotopically zoned carbonate cements record the thermal and chemical conditions of pore fluids during the burial process. The difference in δ 18 O values between the early and late precipitation (i.e., Δ 18 O [early–late]) of 11.9‰, and the difference in δ 13 C values (i.e., Δ 13 C [early–late]) of 11.7‰, reveal significant changes in precipitation temperatures and the availability of carbon sources, respectively. Early-stage precipitation occurred in association with microbial methanogenesis at lower temperatures (~25 °C) during shallow burial (~300 m), whereas late-stage precipitation was related to thermally-induced decarboxylation at higher temperatures (~90 °C or ~110 °C) during deep burial (~2500 m or ~3200 m). These two stages of dissolved pore-filling precipitation correspond to two major periods of dissolution (i.e., eogenetic and mesogenetic dissolution). Diagenetic fluids, mainly CO2 and/or organic acids, were derived from the biological and thermal degradation of organic matter, respectively. These results constrain the isotopic responses of carbonates to organic matter degradation with increasing burial depth and provide significant insights into carbonate diagenesis in organic-rich sedimentary sequences. Highlights: SIMS O and C isotopes constrain the timing and fluid sources of carbonate diagenesis. Large elemental and isotopic variations are recorded in zoned carbonate cements. A shift from microbial methanogenesis to thermally-induced decarboxylation is revealed. Biological and thermal degradation of organic matter influence diagenetic fluids.